An introduction to Yokai culture monsters, ghosts, and outsiders in Japanese history - Komatsu, Kazuhiko 1947-; Yoda, Hiroko; Alt, Matt (2017)
"Since ancient times, the Japanese have lived with superstitions of strange presences and phenomena known as "yokai," creating a culture by turns infused with unease, fear, and divinity. Tsukimono spirit possessions. Fearsome kappa, oni, and tengu. Yamauba crones. Ghostly yurei. Otherworldly ijin ... Where did they come from? Why do they remain so popular Written by Japan's premier scholar of yokai and strange tales, this book is both an introduction to the rich imagination and spirituality of Japan's yokai culture and a history of the authors and writings that have shaped yokai studies as a field"--Back cover.
What is yokai culture? -- Yokai beyond time and borders -- Tsukimono -- Yokai -- Kappa -- Oni -- Tengu and Yamauba -- Yurei -- Ijin and Ikenie: outsiders and sacrifices -- Boundaries.
Translation of: Yokai bunka nyumon.
Includes bibliographical references (pages 176-192)
Japan Foundation
Translated from the original Japanese into English.
Keywords: Demonology -- Japan; Ghosts -- Japan